U-model based controller design for an unmanned free swimming submersible (UFSS) vehicle under hydrodynamic disturbances - Abbasi, I. (National Institute of Science Communication and Information Resources (NISCAIR), 2017)
This paper presents design and implementation of the U-model based controller for controlling pitch angle and heading of an unmanned free swimming submersible vehicle. It is shown that the U-model can adaptively model dynamics of unmanned free swimming submersible and since the U-model is a control oriented scheme, a simple law based on internal model control is used to synthesize the control input. Performance of designed controller is evaluated under hydrodynamic disturbances caused by water current. Further, the performance of proposed scheme is compared with the traditional PID. Both controllers give satisfactorily performance with the U-model performing better in terms of settling time and steady state error. © 2017, National Institute of Science Communication and Information Resources (NISCAIR). All rights reserved.